Analysis of drug allergies in the hospital 'Paolo Giaccone' in Palermo. Issue 2 (12th March 2012) - Pasquale, A.; Capuano, G.; Taormina, E.; Seta, C. La
Abstract : Background: Allergies to drugs and xenobiotic compounds constitute a large part of the iatrogenic effects induced by therapy. It was desired to evaluate the skin reactions of patients in the period July 2010-February 2011 who had regular admission to the dermatology Unit at the Company, classifying them on the ground of event, involved body area and therapeutic class of drugs. Purpose: Study the incidence of Allergies to drugs at Policlinico Paolo Giaccone. Materials and methods: The data was derived from analysis of the first cycles delivered in accordance with law 405/2001 and subsequent verification with the data recorded on patient records. Results: 72 adverse drug reactions were detected. The sample consisted by 35% men and 65% women classified into three age groups 0-30 years (28%) 31-50 (24%) and over 51 years (48%). It is possible to have more detailed information for only 53 adverse reactions among the 72 considered. The authors wanted to investigate the habits of patients and, among 53 cases analysed, 17 cases were smokers, 31 were non-smokers and 5 cases were not recorded. As regards taking of alcoholic beverages, 10 patients regularly consumed alcohol, 34 were abstinent and for 9 the datum was not available. The main clinical manifestations observed were erythema (41 cases), oedema (9 cases), pruritus (34 cases), erythema more other (5 cases), other (3 cases). Events against the trunk were 21 with a prevalence of pruritic erythematous pomfoidi lesions; in the face were two manifestations such as angioedema; in the limbs were 19 events with pomfoidi itchy rash lesion, 6 of which also affect the trunk. It was registered 21 demonstrations against the trunk, with a prevalence of pruritic erythematous pomfoidi lesions; 2 events against the face (angioedema), 19 manifestations against the limbs with erythematous pruritic pomfoidi events among these 6 also interested the trunk, 11 against trunk and face, 2 against face and limbs and 3 against trunk, limbs and face. Classes of drugs that presented major adverse effects were FANS due to ketoprofen (17 cases) followed by nimesulide, ibuprofen and diclofenac with 5, 3 and 2 respectively, followed by analgesics-antipyretics drugs (paracetamol in the foreground followed by metamizole) and ASA on a par with food supplements and lipolytic substances. 47% of adverse reactions was attributable to a single product, 49% to groups of 2 or more drugs, the remainder has not been possible to identify the cause. Conclusions: Given the stochastic nature of the allergic event it was not possible to uniquely identify a relationship between the habits of life of patients and the occurrence of adverse reaction. It is important to point out how the events are more represented for wider access medicines for which it would be necessary to propose awareness-raising and information campaigns for all users who access the structure in order to disadvantage the misuse.